International Migration, Remittances and Labour Force Participation of Left-behind Family Members: A Study of Kerala. (February 2016) - Khan, M. Imran; Valatheeswaran C.,
The article examines the impact of international migration on the labour supply of male and female left-behind household members in both market and non-market work. In addition, we examine the labour supply behaviour of women whose husbands have migrated abroad. After controlling for potential endogeneity using the instrument variable (IV-probit) approach, estimates show that the supply of male and female left-behind members in market work decreases. While international migration results in the relocation of labour supply of male left-behind members from salary and casual wage workers to self-employed workers, it increases female left-behind members' participation in household duties and reduces their participation in unpaid family work. The heterogeneity effect confirms that the impact of international migration is greater in rural than in urban areas. JEL Classification: F22, F24, J21, J24, J16, J61